2014
DOI: 10.1093/femsec/fiu032
|View full text |Cite
|
Sign up to set email alerts
|

Methane dynamics in an alpine fen: a field-based study on methanogenic and methanotrophic microbial communities

Abstract: Wetlands are important sources of the greenhouse gas methane (CH4). We provide an in situ study of CH4 dynamics in the permanently submerged soil of a Swiss alpine fen. Physico-chemical pore water analyses were combined with structural and microbiological analyses of soil cores at high vertical resolution down to 50 cm depth. Methanotrophs and methanogens were active throughout the depth profile, and highest abundance of active methanotrophs and methanogens [6.1 × 10(5) and 1.1 × 10(7) pmoA and mcrA transcript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
32
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(39 citation statements)
references
References 60 publications
7
32
0
Order By: Relevance
“…The results showed that variability in the parameters analyzed was most pronounced in the upper 15 to 20 cm below the water table in these particular fens. At the Oberaar site, composition analysis of methanotrophic and methanogenic communities also confirmed this high variability in the upper soil layers (40). Nevertheless, variations in microbial communities with different dominant species of vascular plants have yet to be investigated.…”
mentioning
confidence: 61%
See 4 more Smart Citations
“…The results showed that variability in the parameters analyzed was most pronounced in the upper 15 to 20 cm below the water table in these particular fens. At the Oberaar site, composition analysis of methanotrophic and methanogenic communities also confirmed this high variability in the upper soil layers (40). Nevertheless, variations in microbial communities with different dominant species of vascular plants have yet to be investigated.…”
mentioning
confidence: 61%
“…Moreover, the submerged mosses Calliergon sarmentosum and Sphagnum spp. are present in patches (32,40).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations